Evaluating Implementation Uncertainties and Defining Safe Operating Spaces for Deeply Uncertain Cooperative Multi‐City Water Supply Investment Pathways - Lillian B. Lau; Patrick M. Reed; David F. Gold (Water Resources Research, 2023)
Abstract Urban water utilities are increasingly exploring cooperative regional water supply investment and management strategies due to climate change and growing demands. Theoretically, regional cooperative agreements promise improved resource efficiency by realizing economies of scale, adding flexibility for achieving improved supply reliability, and, ideally, limiting individual and collective financial risks. However, there has been little research exploring how implementation uncertainties in the partners' cooperative actions shape infrastructure investment and management pathways' robustness and drive counterparty risks. Counterparty risks potentially exacerbate collaborating partners' vulnerability to the supply and financial challenges they initially sought to mitigate through cooperation. To address these concerns, we introduce the safe operating spaces (SOS) for Deeply Uncertain Water Supply Pathways (DUSOSPathways) framework. The framework, demonstrated on the multi‐city Sedento Valley benchmarking test case, facilitates the formal characterization of the effects of implementation uncertainty within cooperative regional water supply investment and management policy pathways. Results demonstrate the path‐dependent effects of implementation uncertainties in short‐term operational drought mitigation instruments and long‐term infrastructure investments. Our analysis further reveals the potential for increased regional conflict due to asymmetries between partners' vulnerabilities to the actions of cooperating partners that can be exacerbated by other deeply uncertain factors that reduce their robustness (e.g., demand growth rates). The study finally delineates SOS, beyond which utilities experience robustness degradation and increased vulnerabilities to future uncertainties to guide implementation of cooperative policy pathways. Overall, this framework is broadly applicable to regional systems seeking to navigate complex cooperative regional water supply investment and management policy pathways.